Die Welt reparieren Open Source und Selbermachen als postkapitalistische Praxis - Baier, Andrea; Hansing, Tom; Müller, Christa; Werner, Karin (Urban Studies, 2016)
Across the world, more and more DIY initiatives are cropping up, in which a diversity of matters and problems are being collectively dealt with. In these collaborative contexts - located away from the market and the state - an understanding of living together and urbanity based around democracy is tested out, and at the same time, ecologically and socially responsible solutions are being sought for fundamental forms of provision of food, of energy, and for making all manner of technology accessible. In the process, fascinating new forms of collective production, repairing and swapping arise which challenge the industrial logic of the 20th century, even turn them on their head. This book is dedicated to the visionary power of these promising innovative practices, and at the same time, provides a societal categorisation of the new `laboratories' of societal transformation. With photographs by Falk Messerschmidt.